2005
DOI: 10.3409/173491605775789353
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Levels of Cellulose in the Diet on the Proteolytic Activity of the Pancreas in Broiler Chickens

Abstract: BOGUS£AWSKA-TRYK M. 2005. Effect of different levels of cellulose in the diet on the proteolytic activity of the pancreas in broiler chickens. Folia biol. (Kraków) 53 (Suppl.): 19-23. The experiment involved 36 Cobb broiler chickens and investigated the effect of different levels of cellulose preparation, Arbocel BWW-40, on the body weight, pancreas weight, content of protein in the pancreas gland and activity of trypsin and chymotrypsin in pancreas. The addition of cellulose to the bird diet showed a signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…Furthermore, they reported significant increases in both pepsin and intestinal aminopeptidase activities in layer pullets offered control diets supplemented with 1.5% levels of dietary Arbocel ® . Although the present work did not test gut enzymatic activity, the improved protein and amino acid digestibility coefficients observed are strongly suggestive of improved digestion and assimilation of nutrients (Boguslawska-Tryk, 2005;Yokhana et al, 2016).…”
Section: Resultsmentioning
confidence: 59%
See 3 more Smart Citations
“…Furthermore, they reported significant increases in both pepsin and intestinal aminopeptidase activities in layer pullets offered control diets supplemented with 1.5% levels of dietary Arbocel ® . Although the present work did not test gut enzymatic activity, the improved protein and amino acid digestibility coefficients observed are strongly suggestive of improved digestion and assimilation of nutrients (Boguslawska-Tryk, 2005;Yokhana et al, 2016).…”
Section: Resultsmentioning
confidence: 59%
“…Correction to zero nitrogen balance was done using the factor 8, 220 cal/g of uric acid nitrogen (Hill and Anderson, 1958). Feed and excreta samples were also analyzed for proximate chemical composition following the methods of the AOAC (1998). The concentration of amino acids, including total sulfur amino acids (TSAA) and tryptophan in the test feed and excreta samples, was determined using HPLC 2690 (Waters Co., Milford, MA).…”
Section: Rooster Digestibility Trialmentioning
confidence: 99%
See 2 more Smart Citations
“…This effect was associated with the significant increase in amylase activity and bile acid concentration in jejunal contents (Hetland et al., ). Moreover, Bogusławska‐Tryk () reported that inclusion of even minor amounts of pure cellulose (0.5–0.7%) into the broiler diet during the rearing period markedly enhanced the content of protein in the pancreas gland and significantly elevated the proteolytic enzymes in pancreatic homogenates. It has been proved that the effect of dietary fibre on secretion of pancreatic enzymes is linked to its direct impact on releasing the hormones of alimentary tract, mainly cholecystokinin (Sánchez et al., ), which in turn stimulates secretion of all pancreas enzymes, including lipolytic ones, and regulates bile flow (Krogdahl, ) facilitating fat digestion.…”
Section: Discussionmentioning
confidence: 99%